2018
DOI: 10.1037/pla0000074
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing child-centered play therapy with children diagnosed with autism spectrum disorder and endured trauma: A case example.

Abstract: Autism spectrum disorder (ASD) is a prevalent childhood disorder as 1 in 68 children, 8 years old and younger, are diagnosed with ASD. Additionally, childhood trauma impacts 60% of children living in the United States. Due to the lack of social awareness and increased sensitivity to various stimuli, children diagnosed with ASD are often more prone to victimization. Current treatment interventions for ASD are limited in flexibility and adaptive qualities. Flexibility is especially important for this population;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…ASD can be difficult to treat because it can be challenging to recognize ASD symptoms and identify an appropriate form of treatment (Guest & Ohrt, 2018). Some counseling interventions, such as cognitive behavioral therapy, have reported improvements; however, these treatments minimize flexibility and the ability to treat in response to the child’s needs at the moment (Guest & Ohrt, 2018). With a child with ASD, mental health professionals need to actively seek approaches that best meet the child’s needs and concerns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ASD can be difficult to treat because it can be challenging to recognize ASD symptoms and identify an appropriate form of treatment (Guest & Ohrt, 2018). Some counseling interventions, such as cognitive behavioral therapy, have reported improvements; however, these treatments minimize flexibility and the ability to treat in response to the child’s needs at the moment (Guest & Ohrt, 2018). With a child with ASD, mental health professionals need to actively seek approaches that best meet the child’s needs and concerns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By explicitly teaching skills, such as positive self-talk, managing emotions, and problem-solving, Mackay, Shochet, and Orr (2017) found that autistic adolescents improved their self-confidence, social skills, ability to cope, and emotional regulation, all of which are known protective factors among non-autistic children (Gartland et al 2019). Similarly, Guest and Ohrt (2018) successfully adapted child-centred play therapy to meet the needs of a five-year-old child on the autism spectrum who had experienced an early traumatic event. The child demonstrated some ability to therapeutically process his traumatic experience, as well as an improvement in impairments related to his autism (Guest and Ohrt 2018).…”
Section: Building Resilience In Children On the Autism Spectrummentioning
confidence: 99%
“…Similarly, Guest and Ohrt (2018) successfully adapted child-centred play therapy to meet the needs of a five-year-old child on the autism spectrum who had experienced an early traumatic event. The child demonstrated some ability to therapeutically process his traumatic experience, as well as an improvement in impairments related to his autism (Guest and Ohrt 2018). Given a better understanding of the experience of resilience and key protective factors in individuals on the autism spectrum, similar interventions, targeting the development of these unique protective factors, may be adapted and provided to children and adolescents on the autism spectrum.…”
Section: Building Resilience In Children On the Autism Spectrummentioning
confidence: 99%
“…The repeated exposure to such events can be traumatic, which may then affect social, physical, and mental health. In one study, for example, about 18.5% and 16.6% of students with autism had experienced trauma‐related abuse and sexual assault, respectively, in their sample survey (Guest & Ohrt, 2018).…”
Section: Introductionmentioning
confidence: 99%